Fire spread simulation using cellular automata in forest fire. Issue 1 (April 2020) - Bhakti, H D; Ibrahim, H; Fristella, F; Faisal, M
Abstract: Forest fires are adverse events both economically and mentally. Triggers of fires are complex variables so that the spread of fire to date has not been predicted. Modeling is one solution to study the process of spreading fire. The Cellular automota was used to simulate the spread of fire in forest fires. Simulations carried out with simulations carried out by varying the value of burnability. burnProbability is a value that shows the probability of a tree burning. The value of burnability used is 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80%. From each burnProbability value, the percentage of forest that is burned is calculated. The simulation was carried out for 17 iterations for each burnProbability value. The results of the average is the greater the value of burnProbability, the greater the percentage of burned forest. When the burnProbability value of 80% of the burned forest is almost entirely, it is 97.23183%.